How to “De-Dutch” the bicycle: Development of active mobility policy on the Caribbean island of Bonaire through real-world mixed methods research - Dylan Power; Meredith Glaser; Rita Gemerts; Desmond Lartey; Bárbara Oliveira Soares (Transportation Research Interdisciplinary Perspectives)
Bonaire, an island in the Dutch Caribbean, faces many societal challenges including poverty, high rates of non-communicable diseases, traffic congestion and physical inactivity. It has been suggested that promoting population levels of walking and cycling can provide a plethora of (co)benefits locally and nationally, especially in areas with low levels of active travel mode share, such as the Global South. In 2024, the Government of the Netherlands invested in a 4-year research project aimed at developing a policy for active mobility on Bonaire. This paper presents the baseline data collected as part of this multi-year pragmatic research project. This study employed a mixed methods approach to understand the current context and active mobility system on Bonaire and investigate current levels and attitudes towards active transport. The methods employed in Year 1 of the project were a repeat cross-sectional survey, observations, stakeholder workshops and interviews and GIS analysis. The findings of this research uncovered that current active mobility levels on Bonaire are low and socioeconomic inequities exist amongst those who do engage in active mobility. Barriers towards transitioning to a less car-oriented mobility system, such as political instability and culture, were identified. However, the active mobility system on Bonaire has many positive elements in its current state which can be capitalised upon. The active mobility system on Bonaire is at a pivotal point and structures to facilitate learning and collaboration across sectors are urgently needed to realise the goal of a thriving active mobility system on the island.